ВОПРОСЫ РАЗВИТИЯ СПОРТИВНОЙ БОРЬБЫ В РЕСПУБЛИКЕ КАРАКАЛПАКСТАН - Халмуратов, М.Т. (SCIENCE and SOCIETY, 2021)
The article is devoted to the development of sports struggle in the Republic of Karakalpakstan. It was emphasized that wrestling is a kind of sport that ensures the harmonious development of the younger generation. Wrestling classes allow to solve a whole range of educational, upbringing and health-improving tasks with high efficiency.